Cardiovascular disease risk in liver transplant recipients transplanted due to chronic viral hepatitis - Paolo Maggi; Federica Calò; Vincenzo Messina; Gianfranca Stornaiuolo; Maria Stanzione; Luca Rinaldi; Stefania De Pascalis; Margherita Macera; Nicola Coppola (PLoS ONE, 2022)
Background Cardiovascular disease (CVD) is a major cause of morbidity and mortality after liver transplantation, mostly in patients transplanted for nonalcoholic steatohepatitis, obesity and diabetes. Few data exist on cardiovascular diseases among patients transplanted for viral hepatitis. Objective Our aim is to clarify the cardiovascular risk and subclinical vascular damage among liver transplant recipients for chronic viral hepatitis (i.e. hepatits C virus, hepatis B virus and hepatitis D virus infection). Methods Adult patients (age ≥ 18 years) with orthotopic liver transplants (OLT) due to viral hepatitis who signed informed consent, and were admitted for a routine follow-up between June 2019 and September 2020 at the Infectious Disease outpatient clinic of the University of Campania Luigi Vanvitelli, Naples, Italy, were prospectively enrolled. An estimation of cardiovascular risk was assessed using three main risk charts, echocolor-Doppler of epiaortic vessels was performed to assess subclinical Intima-Media changes. Results A total of 161 patients were evaluated; of these 15 were excluded because not affected by viral hepatitis. 146 patients were considered. 83 patients (56.8%) were considered at high cardiovascular risk according to Framingham, 54 patients (36.9%) to American Heart Association Arteriosclerotic Cardiovascular Disease (ASCVD) score and 19 (13.0%) to Heart Score. Only 8 patients (5.4%) showed a normal carotid ultrasound, while 52 patients (35.6%) had a carotid artery Intima-Media Thickness (IMT) and 86 (58.9%) an atherosclerotic plaque. Conclusions Liver transplant recipients for virus-related associated liver disease are, in light of the high percentage of carotid lesions, at high risk of CVD. Risk charts compared to subclinical carotid lesions which represent damage already established and a real localization of the disease, seem to underestimate the cardiovascular risk. A chronic inflammatory status, could play a key role. It’s important to raise the awareness of cardiovascular risk in liver transplant patients to prevent cardiovascular diseases and improve the timing of early diagnosis of premature vascular lesions.